Integrin Cross-talk in Endothelial Cells Is Regulated by Protein Kinase A and Protein Phosphatase 1 - Gonzalez, Annette M. (American Society for Biochemistry and Molecular Biology, 2008)
In endothelial cells (ECs) β1 integrin function-blocking antibodies inhibit αvβ3 integrin-mediated adhesion to a recombinant α4-laminin fragment (rα4LN fragment). β1 integrin sequestration of talin is not the mechanism by which β1 integrin modulates αvβ3 integrin ligand binding. Rather, treatment of the ECs with β1 integrin function-blocking antibodies enhances cAMP-dependent protein kinase (PKA) activity and increases β3 integrin serine phosphorylation. The PKA inhibitor H-89 abrogates the effect of β1 integrin function-blocking antibodies on β3 integrin serine phosphorylation and EC-rα4LN fragment binding. β3 integrin contains a serine residue at position 752. To confirm the importance of this residue in αvβ3 integrin-rα4LN fragment binding, we mutated it to alanine (β3S752A) or aspartic acid (β3S752D). Chinese hamster ovary (CHO) cells expressing wild type or β3S752A integrin attach robustly to ligand. CHO cells expressing β3S752D integrin do not. Because the β3 cytoplasmic tail lacks a PKA consensus site, it is unlikely that PKA acts directly on β3 integrin. Instead, we have tested an hypothesis that PKA regulates β3 integrin serine phosphorylation indirectly through phosphorylation of inhibitor-1, which, when phosphorylated, inhibits protein phosphatase 1 (PP1). Treatment of ECs with β1 integrin function-blocking antibodies significantly increases phosphorylation of inhibitor-1. Furthermore, blocking PP1 activity pharmacologically inhibits αvβ3-mediated cell adhesion to the rα4LN fragment when both PKA and β1 integrin function are inhibited. Concomitantly, there is an increase in serine phosphorylation of the β3 integrin cytoplasmic tail. These results indicate a novel mechanism by which β1 integrin negatively modulates αvβ3 integrin-ligand binding via activation of PKA and inhibition of PP1 activity.